1985
DOI: 10.1095/biolreprod33.3.569
|View full text |Cite
|
Sign up to set email alerts
|

Active Immunization of Gilts against Gonadotropin-releasing Hormone: Effects on Secretion of Gonadotropins, Reproductive Function, and Responses to Agonists of Gonadotropin-releasing Hormone1

Abstract: Sexually mature gilts were actively immunized against gonadotropin-releasing hormone (GnRH) by conjugating GnRH to bovine serum albumin, emulsifying the conjugate in Freund's adjuvant, and giving the emulsion as a primary immunization at Week 0 and as booster immunizations at Weeks 10 and 14. Antibody titers were evident by 2 wk after primary immunization and increased markedly in response to booster immunizations. Active immunization against GnRH caused gonadotropins to decline to nondetectable levels, gonada… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
0

Year Published

1986
1986
2008
2008

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 74 publications
(39 citation statements)
references
References 21 publications
2
37
0
Order By: Relevance
“…Recently, however, it has been reported that active immunization against LHRH in gilts resulted in decreased plasma levels of gonadotropins and gonadal steroids, with cessation of estrous cyclicity (Esbenshade and Britt, 1985).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, however, it has been reported that active immunization against LHRH in gilts resulted in decreased plasma levels of gonadotropins and gonadal steroids, with cessation of estrous cyclicity (Esbenshade and Britt, 1985).…”
Section: Discussionmentioning
confidence: 99%
“…The manipulation of the reproductive activity through the use of a GnRH vaccination was first developed for farm animals as this method offers an alternative to surgical castration for minimizing sexual and aggressive behaviour, suppressing reproductive function and preventing pregnancy (Esbenshade and Britt 1985). Several studies investigating the effect of GnRH vaccination have been carried out on mares, some documenting effective suppression of ovarian function and oestrous behaviour along with a subsequent reversal of these effects (Tshewang et al 1997), while others documented greater individual variation and a less reliable result (Dalin et al 2002).…”
Section: Immunization Against Gnrhmentioning
confidence: 99%
“…A radioimmunoassay procedure described by Guthrie & Bolt (1983) and modified by Esbenshade & Britt (1985) was used to determine concentrations of follicle-stimulating hormone (FSH). Anti-pFSH (USDA-10-1010), 125I-labelled pFSH (USDA-FSH-PP1) and pFSH (USDA-FSH-B-1) were used as the first antibody, radiolabelled ligand and standard, respectively.…”
Section: Introductionmentioning
confidence: 99%